PERBANDINGAN RERATA PENGARUH PROGRESSIVE MUSCLE RELAXATION DENGAN GUIDED IMAGERY PADA PENURUNAN TEKANAN DARAH PENDERITA HIPERTENSI - Rachmat Susanto (Jurnal Bina Cipta Husada, 2023)
Many complementary therapies can be applied to lower blood pressure in people with hypertension, including relaxation therapy. Progressive Muscle Relaxation (PMR) and Guided Imagery are two relaxation therapies that are often used to lower blood pressure. However, it is not yet known how far the average comparison of the two relaxation therapies is in reducing blood pressure. This condition raises the question of which one is more effective and efficient in lowering blood pressure so that the risk due to increased blood pressure can be reduced. This study aims to identify the average comparison of the effects of the two relaxation therapies on blood pressure. The research method used was True Experiment Design with the Pre Test-Postest Control Group Design type with the number of respondents in the intervention group and the control group each being 26 respondents with hypertension. Data were analyzed by independent t test. The results of the study in the PMR group showed a decrease in the systolic mean -5.62 mmHg and -4.46 mmHg diastolic while in GI there was a decrease in the systolic mean -4.2 mmHg and a decrease in diastolic -3.22 mmHg. Conclusion PMR lowers blood pressure than GI. Keywords: Progressive Muscle Relaxation, Guided Imagery, Blood Pressure.